Method for producing aramid solution

JP2024518027A5Active Publication Date: 2025-02-20TEIJIN ARAMID BV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023562198
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-15
Filing Date
2022-04-12
Publication Date
2025-02-20
Estimated Expiration
2042-04-12

AI Technical Summary

Technical Problem

Existing methods for producing aramid solutions struggle to achieve high aramid concentrations efficiently and in a timely manner, often requiring dilute solutions followed by concentration steps, and do not fully deprotonate amide bonds in the polymer chains.

Method used

A method involving the use of a solvent and a strong base in chemical equilibrium, combined with aramid materials under high shear conditions, to create a solution with high aramid content, ensuring complete deprotonation of amide bonds and achieving concentrations up to 25% by weight in a short time.

Benefits of technology

The method enables rapid production of high-concentration aramid solutions with complete deprotonation of amide bonds, suitable for processing into various materials like aramid fibers and films, with enhanced mechanical properties and optical anisotropy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present application relates to a method for producing a solution of aramid comprising: i) combining a solvent and a base to obtain a solvent-base mixture; ii) adding an aramid material to the solvent-base mixture to obtain a composition; and iii) mixing the composition to obtain a solution of aramid, wherein at least 1 mole of base is added per liter of solvent to obtain the solvent-base mixture. The invention also relates to the aramid solution, a method for further processing the solution, and continuous aramid fibers having high elongation.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to methods for producing solutions of aramids, solutions comprising aramids, and methods for further processing the solutions into continuous aramid fibers, aramid nanofibers, or aramid films, and also to materials comprising continuous aramid fibers, and aramid nanofibers.

[0002] EP 0 309 229 A1 describes the preparation of articles from isotropic and anisotropic solutions of aromatic polyamide anion salts (e.g. potassium or sodium salts) in liquid sulfoxides such as DMSO. The solutions can be processed into fibers, films and coatings. Aramid solutions are generally prepared at about 1.5-1.7% solids by weight. Solutions with higher polymer contents, up to 12% by weight, can be obtained, for example by evaporating the solvent in vacuum or by freeze-drying.

[0003] EP 1 631 707 A1 describes a non-fibrous para-aramid solution having a high relative viscosity. The solution contains a polar amide solvent, an alkali or alkaline earth chloride, water and 1-8 wt. % aramid. The solution exhibits anisotropic behavior and can be processed by jet spinning to obtain pulp-like fibers.

[0004] US 2013 / 0288050 describes a method by which macro-scale aramid fibers can be dissociated into aramid nanofibers (ANFs). To obtain aramid nanofibers, macro-scale aramid fibers are combined with a solution containing a base (KOH) and an aprotic solvent (DMSO) and stirred. Traces of macro-scale aramid fibers are present in the suspension. The process of forming a suspension of aramid nanofibers takes a very long time (several days).

[0005] WO 2017 / 117376 discloses a method for preparing branched ANFs by adjusting the reaction medium containing aprotic components, protic components and bases. The concentration of aramid and base relative to the amount of solvent is low. The reaction time is generally on the order of days or weeks.

[0006] CN110055797 describes a method for preparing aramid nanofibers, which involves adding para-aramid fibers and KOH to DMSO, subjecting the mixture to ultrasonic treatment, adding water, sealing the suspension, and stirring to obtain aramid nanofibers. This method allows the addition of a larger amount of para-aramid fibers (up to 4 wt%) and a shorter reaction time (e.g., 12 hours).

[0007] China Patent Publication No. 103937237 discloses a method for preparing a para-aramid nanofiber solution with an aramid concentration of 0.05-3.6 wt%, where the para-aramid nanofiber has a diameter of 20-50 nm and a length of 2 μm-10 μm. In this method, the amount of deprotonation reagent mixed with DMSO is 0.42-33.5 mmol, and the dissolution process takes 6-72 hours, with a low aramid concentration example requiring at least 36 or 48 hours of dissolution time, and an aramid concentration of 3.6 wt% requires 72 hours of dissolution time.

[0008] It is desirable to prepare solutions with higher aramid concentrations and obtain anisotropic solutions of aramid from aramid materials that can be processed into various materials, including aramid nanofibers and aramid continuous fibers. It is particularly important to obtain such solutions with high aramid content in a short time. Preferably, such a process does not require first preparing a dilute aramid solution to dissolve the aramid and then concentrating the solution.

[0009] This relates to a method for producing a solution of aramid according to the present invention, comprising the steps of: i) combining a solvent and a base to obtain a solvent-base mixture; ii) combining an aramid material with a solvent-base mixture to obtain a composition; iii) mixing the composition to obtain a solution of aramid; Including, Adding at least 1 mole of base per liter of solvent to obtain a solvent-base mixture; This is possible through the method.

[0010] The aramid material may include aramid fibers (including but not limited to continuous aramid fibers, discontinuous aramid fibers), aramid pulp, aramid film, aramid paper, aramid fibrids, aramid polymer particles (e.g., powder or crumb) and any combination thereof. The aramid material may include aramid obtained from recycling, and even aramid based on post-consumer materials or production waste. Preferably, the aramid material used as the starting material includes discontinuous aramid fibers. The discontinuous aramid fibers preferably have a length (or maximum dimension) ranging from 0.1 mm to at most 100 cm, preferably at most 50 cm, more preferably at most 20 cm, even more preferably at most 10 cm, or even 5 cm.

[0011] A fibre is understood to be a relatively flexible unit of material having a high ratio of length to width (across the cross-sectional area perpendicular to the length).

[0012] In the context of this application, the term "length" refers to the length-weighted length (LL) for short fibers and the average length for longer fibers. For short fibers (and pulps, fibrils and fibrids) up to 6 mm in length, including particles <250 microns in length, the length-weighted length can be determined using a Pulp Expert™ FS (Metso).

[0013] For longer fibers (>6 mm), length refers to the number average fiber length (mean length, ML)

number

[0014] The aramid fibers may be in the form of short cuts.

[0015] Short cuts include short filaments and can be obtained, for example, by cutting a continuous yarn, fabric or woven cloth.

[0016] Aramid materials may include pulp, which consists of short fibers subjected to shear forces that result in the formation of fibrils, most of which remain connected to the "axis" of the original fiber, but the thinner fibrils are detached from the thicker ones. These fibrils are curled, sometimes ribbon-like, and of various lengths and thicknesses.

[0017] In one embodiment, the aramid short cut fibers have a length in the range of 0.1 to 20 mm, preferably 1 to 10 mm, and more preferably 3 to 8 mm.

[0018] Preferably, the aramid short cuts have a narrow length distribution.

[0019] In one embodiment, the length distribution of the aramid short cuts is such that at least 50% by weight of the filaments have a length within 30% of the length of the peak maximum in the length distribution curve.Preferably, at least 70% by weight of the filaments have a length within 30% of the length of the peak maximum in the length distribution curve.

[0020] In the context of this specification, aramid refers to aromatic polyamides consisting of aromatic moieties directly bonded to each other through amide fragments. Methods for synthesizing aramids are known to those skilled in the art and typically involve the polycondensation of aromatic diamines with aromatic diacid halides. Aramids can exist in meta and para forms. Preferably, the aramid material is a para-aramid material.

[0021] For purposes of this application, the term para-aramid refers to a class of fully aromatic polyamide polymers and copolymers having at least 60%, preferably at least 80%, and more preferably at least 90% para-oriented bonds between aromatic moieties. In one embodiment, at least 95% or all (i.e., 100%) of the bonds are para-oriented bonds. Examples of para-oriented aromatic diamines that can be used in the present invention include paraphenylenediamine, 4,4'-diaminobiphenyl, 2,6-naphthalenediamine, 1,5-naphthalenediamine, and 4,4'-diaminobenzanilide. Up to 50 mole % of substituted aromatic diamines such as 2-methyl-paraphenylenediamine and 2-chloro-paraphenylenediamine can be used. Examples of para-oriented aromatic dicarboxylic acid halides that can be used in the present invention include terephthaloyl dichloride, 4,4'-benzoyl dichloride, 2,6-naphthalenedicarboxylic acid dichloride, and 1,5-naphthalenedicarboxylic acid dichloride.

[0022] Typical para-aramids are poly(paraphenylene terephthalamide) (PPTA), poly(4,4'-benzanilide terephthalamide), poly(paraphenylene-4,4'-biphenylenedicarboxamide) and poly(paraphenylene-2,6-naphthalenedicarboxamide), 5,4'-diamino-2-phenylbenzimidazole or poly(paraphenylene-co-3,4'-oxydiphenylene terephthalamide), or copolymers thereof. Preferably, the aramid material comprises or consists of poly(paraphenylene terephthalamide).

[0023] The solvent is an aprotic solvent, preferably a polar aprotic solvent.

[0024] In one embodiment, the solvent is selected from dimethylsulfoxide (DMSO), dimethylformamide (DMF), dichloromethane (DCM), dimethylacetamide (DMAc or DMA), tetramethylurea or N-methyl-2-pyrrolidone (NMP), or a mixture thereof.

[0025] Preferably, the solvent is DMSO.

[0026] The solvent is not sulfuric acid. Preferably, the solvent is free of alkali and alkaline earth salts, especially chlorides.

[0027] The base is preferably a strong base, preferably a base having a dissociation constant pKa (in water) of at least 10, more preferably a base having a dissociation constant pKa of at least 11. Such bases include, for example, oxides of alkali metals.

[0028] In one embodiment, potassium hydroxide (KOH), sodium hydroxide (NaOH), potassium ethoxide (EtOK), sodium hydride (NaH), potassium tert-butoxide (tBuOK), potassium hydride (KH) or sodium amide (NaNH2) is used as the base.

[0029] In one embodiment, DMSO is used as the solvent and KOH as the base.

[0030] In one embodiment of the method, at least 1.5 moles of base per liter of solvent, or preferably at least 2 moles of base per liter of solvent, more preferably at least 2.5 moles of base per liter of solvent, or at least 3 moles per liter of solvent, are added to obtain a solvent-base mixture. In one embodiment, at least 4 moles of base per liter of solvent are even added. An additional amount of base may be added to the composition. To this end, at least 1 mole of base per liter of solvent or at least 1.5 moles of base per liter of solvent is first combined with the solvent. Then, an additional amount of base is added to the composition or is added when forming a solution.

[0031] In the present method, the solvent-base mixture is in chemical equilibrium before being combined with the aramid material. Thus, the solvent-base mixture is in chemical equilibrium before the aramid material is added to the solvent-base mixture. Chemical equilibrium is achieved by the addition of a large amount of base, usually an excess of base. At chemical equilibrium, the reaction quotient (the quotient of the amount of reaction product and the amount of reactant) is constant over time at a particular temperature and pressure and is equal to the equilibrium constant. Thus, the base is dissolved in the solvent (e.g., up to saturation), and the concentration of the base dissolved in the solvent essentially does not change over time at a given temperature. In particular, the cations derived from the base (e.g., KOH when using KOH as the base) are dissolved in the solvent, and the concentration of the base dissolved in the solvent is essentially constant over time at a given temperature. + ), and anions derived from the solvent (dimsil when DMSO is used as the solvent). - The concentrations of the base (e.g., KOH) and solvent (e.g., DMSO) preferably remain constant at a certain temperature and pressure. Depending on the amount of base added to the solvent, there may be an excess of undissolved solid base in the solvent-base mixture and / or composition and / or solution. The base and solvent can be mixed by stirring. Preferably, when using DMSO as the solvent, the aramid material is added only after the dimsyl ions are formed.

[0032] In one embodiment, the solvent and / or the composition and / or the suspension comprises at most 10% by weight of proton donor, preferably at most 5% by weight, more preferably at most 2% by weight or even at most 1% by weight of proton donor, based on the weight of the solvent and / or of the solvent-base mixture and / or of the composition and / or of the solution. More preferably, the content of proton donor is at most 0.5% by weight or even at most 0.2% by weight. The proton donor is, for example, water or an alcohol, for example ethanol, or an acid.

[0033] Low proton donor or water content can be achieved by using analytical grade or nitrogen flushed solvents and running under a N2 atmosphere.

[0034] In one embodiment, the composition is subjected to shear, preferably strong shear, to improve the disintegration and subsequent dissolution of the aramid material. This can improve the dissolution of the aramid material. Shear can be applied by vigorous stirring, kneading or ultrasonic treatment of the composition. Ultrasonic treatment can be used at frequencies ranging from 10 to 50 kHz, preferably 15 to 25 kHz.

[0035] The dissolution of the aramid material is preferably carried out at room temperature or slightly elevated temperatures, but below 50° C., preferably below 40° C., more preferably below 35° C., to avoid (hydro)decomposition of the polymer. Preferably, the dissolution of the aramid material is carried out at a temperature of at least 15° C., preferably at least 18° C.

[0036] In one embodiment, at least step iii) of the process (mixing the composition) is carried out in a mixer, in particular a high shear mixer, such as a twin screw kneader, twin screw extruder, twin shaft kneader or mixer, single screw kneader or single screw extruder, or a Drais mixer. Preferably, steps ii) and iii) are carried out in a high shear mixer, such as a twin screw kneader, twin screw extruder, twin shaft kneader or mixer, single screw kneader or single screw extruder, or a Drais mixer.

[0037] Particularly for large scale processes, the use of such equipment has been found to be advantageous in generating sufficient shear, employing shorter mixing times, and allowing for continuous processing.

[0038] For large scale processes, the following method embodiment can be used: The solvent and a specified amount of base are stirred at room temperature in a vessel with (high) shear to reach chemical equilibrium. The solvent-base mixture is introduced into a mixer, for example a twin-screw extruder. The twin-screw extruder can have separate inlets for the liquid solvent-base mixture and the solid aramid material. The liquid solvent-base mixture can be introduced under high pressure and combined with the solid aramid material. Preferably, the solid aramid material is dosed into the extruder before the addition of the liquid solvent-base mixture. Optionally, an additional amount of base is added to the extruder, either in solid form or in its aqueous solution. Such additional amount of base can be added, for example, downstream of where the solvent-base mixture is added to the extruder. The amount of aramid material and solvent-base mixture is desirably adjusted to obtain a final polymer concentration of at least 5% by weight, preferably 7-22% by weight, more preferably 10-20% by weight, and even more preferably 12-18% by weight. The process in the (twin-screw) extruder is preferably carried out at a temperature of at most 50° C., preferably at most 25° C. (cooling may be applied if necessary). The mixing time is adjusted by adjusting the feed rate and the exit flow (extrudate). Rotation speeds of up to, for example, 300 rpm can be used to achieve high shear. The screw configuration of the extruder can be constructed with many different elements, such as conveying, mixing and kneading elements.

[0039] Preferably, the following screw configurations can be used: the entry zone elements have a length of preferably 3-6D (D represents the diameter of the screw in mm), can have a length of about 6-9D, and comprise conveying elements that are single- or double-start threads. Single-start and double-start screw elements are known conveying elements that do not cause compaction during conveying. The mixing and dissolving zone can have a length of 15-30D, preferably 20-23D, and elements without conveying properties (screw elements such as Igel or Hedgehog and / or single-row / multiple-row tooth mixed ZME from W&P; single-row or multi-row tooth mixed ZB from Berstorff, and multi-row tooth mixed BMEL from Clextral) or elements with intermittent conveying properties (screw elements such as SME type from W&P or EAZ-ME type from Berstorff) are used. Mixing elements without conveying properties are characterized in that they do not cause conveying and are therefore completely filled with product and have dispersive mixing properties. Mixing elements with intermittent conveying properties have channels with conveying properties. These elements have distributive mixing properties and do not need to be completely filled.

[0040] Alternatively, the following screw configurations can be used: the entry zone element has a length of 2-10D, preferably 5-7D (D represents the diameter of the screw in mm).

[0041] The mixing and dissolving zone can have a length of 10-20D, preferably 13-16D, and elements with conveying properties are used. The degassing zone can have a length of 3-8D, preferably 2-4D, and negative conveying elements as vacuum locks and positive conveying elements at the vacuum connection of the (twin-screw) extruder are used.

[0042] The mixing and compression zone can have a length of 10-30D, preferably 16-19D, and elements having transport or compression properties are used.

[0043] Optionally, a vacuum (negative pressure) can be applied in the extruder to remove any gases and obtain a gas-free aramid solution suitable for further processing. Preferably, the extrudate is collected in a closed container or barrel (to exclude the presence of proton donors, e.g., moist air).

[0044] Optionally, large undissolved base particles, e.g., particles having a size greater than 0.5 μm, are removed from the solvent-base mixture prior to combining the aramid material with the solvent-base mixture. In large-scale processes, removal of large undissolved base particles can be performed (e.g., by settling, decanting, or filtration) prior to introducing the solvent-base mixture into a mixing device.

[0045] Optionally, undissolved aramid material is removed from the solution of aramid, for example by settling, decanting or filtration.

[0046] For this method, the concentration or amount of aramid material in the composition can be at least 1% by weight, preferably at least 2% by weight, more preferably at least 4% by weight, and even more preferably at least 4.5% by weight, based on the weight of the composition. The concentration of aramid material in the composition can also range up to 25% by weight. Preferably, the concentration of aramid material in the composition is at least 10% by weight.

[0047] Preferably, the concentration of aramid in such dissolved solution is in the same range.

[0048] In one embodiment, the aramid material is combined with the solvent-base mixture by combining the aramid material with the solvent-base mixture in at least two steps, preferably at least three steps, and more preferably at least four steps. Preferably, the amount of aramid material added in one step ranges from 0.1 to 2% by weight based on the weight of the solution.

[0049] For example, an amount of aramid material in the range of 0.5% to 1% by weight of the solution can be added per step. Agitation or sonication may be applied between steps. The amount of aramid material added per step may be distributed evenly across the number of steps (e.g., 1 / 3 for each of 3 steps) or the amount may vary between steps (e.g., increased or decreased between steps).

[0050] In one embodiment, a total of at least 2 moles of base per liter of solvent is added to prepare a solvent-base mixture and at least 2.5 weight percent of the aramid material is combined with the solvent-base mixture to obtain a solution, preferably at least 2.5 moles of base and at least 4 weight percent of the aramid material per liter of solvent.

[0051] The advantage of this method is the short time required to obtain an aramid solution. The first method step, i.e. combining the base and the solvent to obtain a solvent-base mixture in chemical equilibrium, preferably takes 2 to 24 hours, depending on the choice of mixing device. This time can be reduced by using a base with a small particle size. The third method step, i.e. mixing the composition to obtain an aramid solution, preferably takes 5 minutes to 2 hours, depending on the choice of mixing device.

[0052] Another subject of the present application is a solution comprising a solvent, a base and an aramid, the solution comprising at least 1 mole of base per liter of solvent, preferably at least 1.5 moles, more preferably at least 2 moles, and even more preferably at least 3 moles of base per liter of solvent.

[0053] In one embodiment, the subject of this application is a solution comprising a solvent, a base and an aramid, where the solution is saturated with respect to the amount of base, so that at a certain temperature and pressure, no more base will dissolve in the solution.

[0054] The solution can be obtained by first adding an excess of base to a solvent to create a solvent-base mixture, removing the excess solid base (e.g., by decanting or filtering the solvent-base mixture), and adding a predetermined amount of aramid.

[0055] Using this method, the solution of aramid (i.e., aramid solution) is a non-fibrous solution in which the amide bonds in the aramid polymer chains are largely, preferably completely, deprotonated. Aramid polymer in crystalline form (undissolved) still contains protons in hydrogen bonds. The protonation state of aramid can be determined by NMR (nuclear magnetic resonance spectroscopy), particularly 1 It can be determined by H-NMR.

[0056] The formation of a red solution indicates dissolution and at least partial deprotonation of the aramid polymer.

[0057] To determine and prove the (complete) deprotonation of aramid by a solvent containing a base, a solution of aramid in a deuterated solvent containing a base was prepared, 1 Determine the presence of amide protons in the H NMR spectrum. For poly(paraphenylene terephthalamide) (PPTA) and DMSO, make a solution of PPTA in DMSO-d6 / KOH and stir at room temperature.

[0058] After dissolution, the sample standards 1 H spectra were recorded on a Bruker Avance III 400 MHz NMR. Quantification was performed from a separately measured solution of DMSO-d6 / KOH containing 10 mg of DMSO using the so-called eretic method, where an internal standard is projected onto the empty region of the sample spectrum. Since DMSO-d6 does not contain exchangeable deuterons, the amide protons are usually projected onto the empty region of the sample spectrum. 1 1H NMR spectrum between 9 and 11 ppm is expected. The absence of such a signal in the spectrum recorded in DMSO-d6 / KOH indicates complete deprotonation of the amide group.

[0059] For this reason,1 PPTA is completely deprotonated in DMSO / KOH solution, as evidenced by the (almost) absence of amide protons (i.e., up to 2 mol %) in the 1 H NMR spectrum.

[0060] Thus, preferably, the aramid solution of the present invention contains at most 5 mol %, more preferably at most 2 mol %, of protonated amide groups as determined above. 1 H} NMR spectra can be recorded to observe and estimate the end group content. Estimations made from 2% (m / m) PPTA in DMSO-d6 / KOH solution give end group contents in the expected range. Therefore, it can be concluded that no degradation of the polymer occurred in the DMSO / KOH solution.

[0061] Prior art methods of preparing aramid nanofiber dispersions, or dispersions of aramid polymers in amide solvents (e.g., NMP) with cosolvents (e.g., CaCl2), or solutions of aramids in sulfuric acid are different from the present solution. Prior art methods produce dispersions of aramid nanofibers or dispersions of aramid polymers in which the amide bonds are not fully deprotonated. In the present solution, the amide bonds are preferably fully deprotonated.

[0062] In a solution of aramid in sulfuric acid, the amide groups in the polymer are protonated. In a solution of NMP with a cosolvent, the ions of the cosolvent (e.g., Ca 2+ ) is attached to the amide group. When a proton donor is used to generate the ANF dispersion, the amide group becomes at least partially protonated.

[0063] In one embodiment, the solution comprises at least 1% by weight of aramid, preferably at least 2% by weight, more preferably at least 4% by weight, and even more preferably at least 4.5% by weight, based on the weight of the solution. The concentration of aramid in the solution may range up to 25% by weight. Preferably, the concentration of aramid material in the composition is at least 10% by weight.

[0064] The concentration of the solution can be selected depending on further processing: for spinning the solution into fibers, relatively high concentrations are preferred (e.g., 5-25 wt%), while for making resin composites, relatively low concentrations can be used (e.g., up to 5 wt%).

[0065] Preferably, the aramid solution exhibits optical anisotropy (liquid crystal behavior), ie, the aramid molecules are densely packed and in an ordered arrangement.

[0066] The optical anisotropy of a solution can be seen when examined under a polarizing microscope (bright image) and / or as an opalescence upon stirring.

[0067] Typically, aramid solutions (at room temperature) containing at least 3% by weight of aramid exhibit optical anisotropy. Higher concentration aramid solutions (e.g., at least 4%, at least 5% or at least 10% by weight) exhibit optical anisotropy.

[0068] Optical anisotropy is sometimes called birefringence.

[0069] The invention also relates to methods of processing the solution into various forms of products or materials, such as continuous aramid fibers, aramid nanofibers, aramid films, or composites containing aramid.

[0070] Thus, the present invention provides a method for producing continuous aramid fibers, comprising the steps of: i) providing a solution produced according to any of the solution or method embodiments as described above; ii) passing the solution through a spinneret; iii) coagulating the solution to obtain fibers; iv) washing the fibers; The present invention relates to a method comprising the steps of:

[0071] Preferably, the spinning process of the method for producing continuous aramid fibers is a dry jet wet spinning process, which means that the solution passes through a gaseous medium after leaving the spinneret and before entering the coagulation bath. Preferably, the solution passes through a gaseous medium. The gaseous non-coagulation medium preferably consists of air.

[0072] The gaseous medium (also called air gap) preferably has a length in the range of 2 to 20 mm, more preferably 3 to 15 mm, and even more preferably 5 to 10 mm.

[0073] The aramid present in the solution is drawn in a gaseous medium through which the solution passes. However, it is also possible to process the solution into continuous fibers without using an air gap in the wet spinning process, so that the solution enters the coagulation bath directly after leaving the spinneret.

[0074] The degree of draw, which is the ratio of the length of the filament as it leaves the coagulation bath to the average length of the solution as it leaves the spinneret's nozzles, may range from 1.5 to 15, preferably 2 to 6.

[0075] After coagulation, the continuous aramid fibers formed are removed from the coagulation bath, washed, dried and wound onto bobbins. The spinnerets themselves used may be of the type known for dry jet wet spinning.

[0076] Surprisingly, it has been found that spinning of an aramid solution, particularly into low titer filaments, and subsequent washing of the filaments allows for efficient removal of the base.

[0077] When a previously unprocessed or shaped para-aramid polymer is used as the starting material (aramid material) to make the solution, the continuous para-aramid fiber obtained by this process does not contain sulfonic acid groups.

[0078] On the other hand, when the aramid material comprises recycled aramid, the continuous para-aramid fibers obtained by this process have sulfonic acid groups.

[0079] The continuous aramid fibers thus produced may have attractive mechanical properties, for example, they may exhibit less fibrillation (higher abrasion resistance), have high elongation at break and / or high resistance to lateral compression.

[0080] The continuous aramid fibers produced by the above process may preferably have an elongation at break of at least 5%, more preferably at least 7.5%, and even more preferably at least 10%. The elongation at break may even be higher than 15%. The elongation at break is determined according to ASTM D7269 after conditioning at 20° C. and 65% relative humidity for 14 hours according to ASTM D1776.

[0081] A subject of the present invention is therefore also continuous aramid fibres, the elongation at break, determined as above, being at least 5%, more preferably at least 7.5%, even more preferably at least 10% or at least 15%.

[0082] Another object of the present invention is a method for producing aramid nanofibers, comprising the steps of: i) providing a solution produced according to any of the solution or method embodiments described above; ii) adding a predetermined amount of a proton donor to the solution; The method includes:

[0083] The proton donor may be selected, for example, from water and an alcohol (eg, ethanol or methanol).

[0084] The aramid nanofibers obtained by this process can be used to coat various substrates, in particular to modify or improve the properties of the substrate or at least the surface properties of the substrate, for example, a coating of the aramid nanofibers can be used to improve the fire resistance of the substrate.

[0085] Additionally, the aramid nanofibers can be used to reinforce composite materials, and in particular the aramid nanofibers can be added to the resin or matrix material of the composite.

[0086] Alternatively, the aramid nanofibers can be used as a filler or adhesive (eg, in sheet-like materials such as paper or in composites).

[0087] Another object of the present invention is a method for producing an aramid film, comprising the steps of: i) providing a solution produced according to any of the solution or method embodiments as described above; ii) dispensing a solution onto a surface; iii) solidifying the solution to form a film; and The method includes:

[0088] In one embodiment, the solution may be combined with a solution of another polymer before being dispensed onto a surface, and the combined solution may be used to produce an aramid film that includes the other polymer.

[0089] The surface can be a substrate surface. Alternatively, the surface is part of an object to be coated with a film of the solution.

[0090] The solution can be applied to the (support) surface, for example by casting from a die or by application with a roller.

[0091] Alternatively, the object to be coated with a film of the solution is immersed in the solution or coated by other methods including spraying or other known methods.

[0092] The solution is then allowed to solidify to form a film, which can be accomplished by drying or coagulation, for which the solution is subjected to an aqueous coagulant, such as water or an aqueous solution of a solvent.

[0093] Preferably, the film is rinsed or washed to remove residual solvent and / or base. The washed film may be stretched and dried. Optionally, the dried film may be heat treated.

[0094] The solutions can also be used in the production of resin composites: they can be combined with resins or added to resin solutions (including, for example, epoxy resins) to improve the mechanical properties of the resin after curing.

[0095] Thus, the present application also relates to aramid nanofibers, aramid films and continuous aramid fibers obtained by any of the methods of processing the aramid solution.Furthermore, the present application relates to materials comprising the aramid nanofibers obtained by the above methods.The materials may be selected from coatings and composites. [Brief description of the drawings]

[0096] [Figure 1] 1 shows SEM images of the films of Example 1 and Example 2 (right image: Example 2, left image: Example 1).

[0097] The invention is further illustrated by the following non-limiting examples.

[0098] Example 1 A solution was formed by dissolving 5.61 g of KOH in 50 mL of DMSO in a sealed 250 mL Erlenmeyer closed with a glass stopper and parafilm after nitrogen flow. The solvent was stirred for 24 hours. The solvent (50 mL) was decanted and placed in a 1 L glass reactor to which 1.68 g of p-phenylene terephthalamide (PPTA, Twaron® 1000 short cut, 6 mm long) was added and stirred for approximately 1.5 hours (corresponding to an aramid concentration of 3 wt%). Dissolution was complete when no visible PPTA fibers were detected by Leica optical microscope using cross polarized light.

[0099] A film was made from the solution. A portion of the solution (one laboratory spoon) was spread on a glass plate by a doctor blade. The glass plate was placed in a demineralized water bath until the film was completely solidified. The film was placed in an alcohol bath to rinse off the water. Finally, the film was dried on the glass plate in a fume hood.

[0100] Example 2 A solution was formed by dissolving 2.80 g of KOH in 50 mL of DMSO in a sealed 250 mL Erlenmeyer closed with a glass stopper and parafilm after nitrogen flow. The solvent was stirred for 24 hours. The solvent (50 mL) was decanted and placed in a 1 L glass reactor to which 1.68 g of PPTA (Twaron® 1000 short cut, 6 mm long) was added and stirred for approximately 3 hours (corresponding to an aramid concentration of 3 wt%). Dissolution was complete when no visible PPTA fibers were detected by Leica optical microscope using cross polarized light.

[0101] A film was made from the solution. A portion of the solution (one laboratory spoon) was spread on a glass plate by a doctor blade. The glass plate was placed in a demineralized water bath until the film was completely solidified. The film was placed in an alcohol bath to rinse off the water. Finally, the film was dried on the glass plate in a fume hood.

[0102] The films of Example 1 and Example 2 were analyzed by scanning electron microscopy (SEM).

[0103] The SEM images are shown in FIG. 1 (right image: Example 2, left image: Example 1).

Claims

1. 1. A method for producing a solution of aramid, comprising the steps of: i) combining a solvent and a base to obtain a solvent-base mixture; ii) combining an aramid material with the solvent-base mixture to obtain a composition; iii) mixing said composition to obtain a solution of aramid; Including, adding at least 1 mole of base per liter of solvent to obtain said solvent-base mixture; method.

2. The method of claim 1, wherein the solvent-base mixture is in chemical equilibrium prior to combining with the aramid material.

3. 3. The process according to claim 1 or 2, wherein at least 1.5 moles, preferably at least 2 moles, more preferably at least 2.5 moles, even more preferably at least 3 moles, or even more preferably at least 4 moles of base are added per liter of solvent.

4. 3. The method according to claim 1 or 2, wherein the solvent and / or the solvent-base mixture and / or the composition and / or the solution comprises at most 10% by weight of proton donor, preferably at most 5% by weight, further preferably at most 2% by weight of proton donor, based on the weight of the solvent and / or based on the weight of the solvent-base mixture and / or based on the weight of the composition and / or based on the weight of the solution.

5. The method of claim 1 or 2, wherein the composition is subjected to shear.

6. 3. The process according to claim 1 or 2, wherein at least step iii) is carried out in a twin-screw kneader or a twin-screw extruder, preferably steps ii) and iii) are carried out in a twin-screw kneader or a twin-screw extruder.

7. 3. The method of claim 1 or 2, wherein the amount of aramid material is at least 1 wt.%, preferably at least 2 wt.%, more preferably at least 4 wt.%, even more preferably at least 4.5 wt.%, and most preferably at least 10 wt.%, based on the weight of the composition.

8. 1. A solution comprising a solvent, a base and an aramid, said solution comprising at least 1 mole of base per liter of solvent, preferably at least 1.5 moles of base per liter of solvent, more preferably at least 2 moles, even more preferably at least 2.5 moles of base per liter of solvent, and even more preferably at least 3 moles of base per liter of solvent.

9. 9. The solution of claim 8, wherein the solution comprises at least 1 wt. % aramid, based on the weight of the solution, preferably at least 2 wt. %, more preferably at least 4 wt. %, even more preferably at least 4.5 wt. %, and most preferably at least 10 wt. % aramid.

10. 10. The solution according to claim 8 or 9, which exhibits anisotropic liquid crystal behaviour.

11. 10. The solution of claim 8 or 9, wherein the aramid contains at most 5 mol %, more preferably at most 2 mol %, of protonated amide groups as determined by nuclear magnetic resonance spectroscopy.

12. 1. A method for producing continuous aramid fibers, comprising the steps of: i) providing a solution according to claim 8 or 9 or a solution produced according to the method according to claim 1 or 2; ii) passing the solution through a spinneret; iii) coagulating the solution to obtain fibers; iv) washing the fibers; A method comprising:

13. A continuous aramid fiber having an elongation at break, determined according to ASTM D7269, of at least 5%, preferably at least 7.5%, more preferably at least 10% or at least 15%.

14. 1. A method for producing aramid nanofibers, comprising: i) providing a solution according to claim 8 or 9 or a solution produced according to the method according to claim 1 or 2; ii) adding a predetermined amount of a proton donor to the solution; A method comprising:

15. A material comprising aramid nanofibers obtainable by the method of claim 14, preferably selected from coatings and composites.

16. 1. A method for producing an aramid film, comprising the steps of: i) providing a solution according to claim 8 or 9 or a solution produced according to the method of claim 1 or 2; ii) dispensing said solution onto a surface; iii) solidifying the solution to form a film; and A method comprising: